Donations and Unpaid Activities - Olaf Hübler (Institute of Labor Economics (IZA), 2023)
Donations and unpaid working are two important forms of non-market activities that are usually considered separately in the literature. The purpose of this paper is to empirically test hypotheses on determinants of giving to organizations. In particular, the importance of voluntary work for giving behavior is examined in comparison to other unpaid activities. In addition, the aim is to find out whether mutual dependencies exist and to what extent benefits, measured by satisfaction, can be derived from both forms. Estimates using data from the Socio-Economic Panel for the years 2019/2020 lead to the following results for Germany: - Personality traits and individual assessment, under which conditions a society is judged to be just, are important for donation behavior. These two aspects are widely neglected in the literature. - If honorary offices are exercised as a major activity, a clear positive donation effect is derived in contrast to a secondary activity. - Participation in citizens' initiatives shows a similar correlation. In contrast, unpaid overtime in professional life shows a negative link. - No effect can be discerned, based on an honorary office, for payments to unrelated individuals. - Donations to organizations and voluntary work show mutual dependencies. - Life satisfaction is increased both by donating and by doing voluntary work.
Keywords: D64; D91; I30; J30; 330; citizens' initiative; donations; life satisfaction; personality traits; unpaid work; volunteering